Advances in tea agronomy - Carr, M. K. V. (Cambridge University Press, 2018)
Tea is big business. After water, tea is believed to be the most widely consumed beverage in the world. And yet, as productivity increases, the real price of tea declines while labour costs continue to rise. Tea remains a labour intensive industry. With a distinguished career spanning over 50 years and rich experience in diverse crops, Mike Carr is eminently qualified to indulge in an intelligent discourse on tea agronomy. In addition to a comprehensive review of the principal tea growing regions worldwide in terms of structure, productivity and principal constraints, he has attempted to question and seeks to find the associated experimental evidence needed to support current and future crop management practices. The book will assist all those involved in the tea industry to become creative thinkers and to question accepted practices. International in content, it will appeal to practitioners and students from tea growing countries worldwide.